2021
DOI: 10.1016/j.jval.2020.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Vignette-Based Utilities: Usefulness, Limitations, and Methodological Recommendations

Abstract: Health technology assessment agencies often prefer that utilities used to calculate quality-adjusted life years in cost-utility analyses (CUAs) are derived using standardized methods, such as generic preference-based measures completed by patients in clinical trials. However, there are situations when no standardized approach is feasible or appropriate for a specific medical condition or treatment that must be represented in a CUA. When this occurs, vignette-based methods are often used to estimate utilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 79 publications
0
38
0
1
Order By: Relevance
“…There are some limitations to this study, mostly related to the use of vignettes. Vignettes are widely used in health services research, and have been shown to reliably represent patients’ clinical experiences, behaviors, and perspectives [ 49 ]. An assumption of the study design was that participants were able to imagine themselves in an exchange with their own PCP similar to the one described in the vignettes.…”
Section: Discussionmentioning
confidence: 99%
“…There are some limitations to this study, mostly related to the use of vignettes. Vignettes are widely used in health services research, and have been shown to reliably represent patients’ clinical experiences, behaviors, and perspectives [ 49 ]. An assumption of the study design was that participants were able to imagine themselves in an exchange with their own PCP similar to the one described in the vignettes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it should also be stressed that these symptoms of AADC deficiency were derived from extensive content validation involving parents and caregivers of, as well as physicians treating AADC deficiency patients. 16 The use of vignettes may have also contributed to this; however, given the rarity of AADC deficiency and the nature of the patients affected (predominantly very young children), this is the only methodology available 27 to generate health state utilities in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The draft methods guide states "If there is evidence that generic measures are unsuitable for the condition or intervention, refer to the hierarchy of preferred sources for health-related quality of life." [34] The hierarchy also includes general information on the design and conduct of vignette studies which is applicable to young children [35,36].…”
Section: Discussionmentioning
confidence: 99%